Genome wide association study of fetal hemoglobin in sickle cell anemia in Tanzania - Mtatiro, SN; Singh, T; Rooks, H; Mgaya, J; Mariki, H; Soka, D; Mmbando, B; Msaki, E; Kolder, I; Thein, S; Menzel, S; Cox, SE; et al. (Public Library of Science, 2014)
BACKGROUND: Fetal hemoglobin (HbF) is an important modulator of sickle cell disease (SCD). HbF has previously been shown to be affected by variants at three loci on chromosomes 2, 6 and 11, but it is likely that additional loci remain to be discovered. METHODS AND FINDINGS: We conducted a genome-wide association study (GWAS) in 1,213 SCA (HbSS/HbSβ0) patients in Tanzania. Genotyping was done with Illumina Omni2.5 array and imputation using 1000 Genomes Phase I release data. Association with HbF was analysed using a linear mixed model to control for complex population structure within our study. We successfully replicated known associations for HbF near BCL11A and the HBS1L-MYB intergenic polymorphisms (HMIP), including multiple independent effects near BCL11A, consistent with previous reports. We observed eight additional associations with P<10(-6). These associations could not be replicated in a SCA population in the UK. CONCLUSIONS: This is the largest GWAS study in SCA in Africa. We have confirmed known associations and identified new genetic associations with HbF that require further replication in SCA populations in Africa.